La Pathologie Anorectale Au Chu Campus De Lome (Togo) - A. Bagny; LM. Lawson-Ananissoh; O. Bouglouga; YR. El Hadji; LY. Kaaga; D. Redah; MA. Djibril (European Scientific Journal, ESJ, 2017)
Objective: To describe the clinical and endoscopic presentation of anorectal pathologies in the gastroenterology department of the CHU campus of Lomé. Patients and methods: Retrospective study based on reports of low digestive endoscopy carried out at the university teaching hospital Campus of Lome. We collected the age of the patients, their sex, the indications of the examination and the different anorectal lesions encountered. Results: The mean age was 41.8 ± 14.3 years. There was a predominance of 30-40 years (38.8%). There was also a male predominance with a sex ratio of 1.6. The most frequent indication was rectal bleeding (64.1%). Anal pain was found in 40.8% of cases. The most frequent lesions were hemorrhoids (69.9%) and anal fistula in 8.7% of cases. Cancer of the anus was rarely observed (1.9%) as was the rectal polyp (0.1%). Conclusion: Anorectal pathologies are relatively frequent in our department, especially in young patients and are dominated by hemorrhoidal disease.